2008
DOI: 10.1186/1471-2407-8-99
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induction in Jurkat cells and sCD95 levels in women's sera are related with the risk of developing cervical cancer

Abstract: Background: Currently, there is clear evidence that apoptosis plays an important role in the development and progression of tumors. One of the best characterized apoptosis triggering systems is the CD95/Fas/APO-1 pathway; previous reports have demonstrated high levels of soluble CD95 (sCD95) in serum of patients with some types of cancer. Cervical cancer is the second most common cancer among women worldwide. As a first step in an attempt to design a minimally invasive test to predict the risk of developing ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
1
3
0
1
Order By: Relevance
“…Apoptosis reduction by 85.4% was observed in Jurakt cells, when induced with sera from CC patients as compared to sera from HC. In agreements to the previous reports (27); these results indicate that CC reduces the apoptotic potential of sera to induce cell death in Jurkat cells.…”
Section: Cervical Cancer Patient's Serum Prevents Apoptosis Induction...supporting
confidence: 93%
See 1 more Smart Citation
“…Apoptosis reduction by 85.4% was observed in Jurakt cells, when induced with sera from CC patients as compared to sera from HC. In agreements to the previous reports (27); these results indicate that CC reduces the apoptotic potential of sera to induce cell death in Jurkat cells.…”
Section: Cervical Cancer Patient's Serum Prevents Apoptosis Induction...supporting
confidence: 93%
“…Reports about the other malignancies also authenticated this data as the elevated levels of sCD95 have been observed in patients' sera samples of ovarian, gall bladder, lung, melanoma, head and neck (29), renal carcinomas (30) as well as autoimmune rheumatic diseases (3). Sera levels of sCD95 has also been well correlated with the survival rate of the CC patients as the lower sCD95 (27), when compared to the patients having higher sCD95 levels (>1.5ng/ml). Present data is in absolute agreement with these reports, equally present study also found very low levels of sCD95 in the sera samples of HC.…”
Section: Discussionmentioning
confidence: 93%
“…Jurkat T cells were grown in RPMI 1640 supplemented with 90 units/ml of penicillin, 90 μg/ml streptomycin, 2 m M L ‐glutamine, and 10% volume/volume heat‐inactivated fetal bovine serum at 37°C in an atmosphere of 5% CO 2 . Jurkat cells were chosen for use in a model of CD95/CD95L‐mediated apoptosis, since previous studies have shown that between 80% and 100% of synovial fluid T cells and Jurkat cells express CD95, compared with only 40% of peripheral blood lymphocytes (27, 28). Synovial fluid T cells and Jurkat cells also have similar surface expression of integrins (29).…”
Section: Methodsmentioning
confidence: 99%
“…The exact mechanism attempting to explain how cellular constituents make their way from the apoptotic cell into serum still remains unclear (10). Several studies have measured circulating levels of sFas and sFasL under various disease states, such as atherosclerosis (12), coronary artery disease (13,14), thyroid-associated ophthalmopathy (15), testicular toxicity (16), renal failure (17), liver disease (18), and cancer (19,20). Cytochrome c has been suggested as a possible serum marker of mitochondria-mediated apoptosis (10,21).…”
mentioning
confidence: 99%